Regularized approximations of singular perturbations from the H_2-class - Koshmanenko, V. D. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
For a sequence of singular perturbations belonging to the H_1-class and converging to a given singular perturbation from the H_2-class, we find a method of additive regularization that guarantees the strong resolvent convergence of perturbed operators.